Mathematics a tool for success of entrepreneurship opportunities (2016)
Mathematics is a compulsory subject taught in both primary and secondary schools in Nigeria. The importance of Mathematics and its applications is all encompassing and that is why the famous status accorded to as everyday subject and its’s centrality in the curriculum. Today, it is a reality that it is the creation, mastery and utilization of modern science and technology that basically differentiates the developing from developed nations of the world. The foundation of science and technology, which is the basic requirement for development of nation, is Mathematics. Therefore, mathematics plays a vital role in nation building and mathematics is very crucial for many careers and job opportunities in today’s increasing technological society. While mathematics is not only for knowledge and understanding, its other objectives includes skill application/development, attitude formation appreciation, problem-solving skill, brevity> generalization, drawing inferences, interpreting, future vocational/ life skills, reasoning ability, systematic and critical thinking and others. Entrepreneurship is a creative and innovative response to the environment such responses can take place in any field of social endeavour, business, industry, agriculture, education, social work and the like. This paper explores the various skills of mathematics as a tool for the creation of success in diverse entrepreneurship opportunities.